Pengaruh Crude Fukoidan dari Ekstrak Sargassum crassifolium terhadap Kadar ICAM-1 dan VCAM-1 pada Sel Raw 264.7 yang Diinduksi Lipopolisakarida - Ayu Werawati; Esti Mumpuni; Kusmardi Kusmardi; Dian Ratih Laksmitawati; Syamsudin Abdillah (Fakultas Farmasi Universitas Pancasila, 2019)
Inflammation is the response of vascular tissue to infection and damaged tissue to remove agents that cause inflammation. Macrophages are the dominant cells in the inflammatory reaction. Adhesion of leukocytes to vascular endothelium is a main feature of the inflammatory process. The presence of adhesion molecules, such as ICAM-1 and VCAM-1, can lead to adhesion of monocytes and lymphocytes to endothelial cells via bonding adhesion molecules to endothelial cells. Crude fukoidan derived from Sargassum crassifolium taken from Garut waters and extracted with dilute HCl, tested for anti-inflammatory activity through inhibition of ICAM-1 and VCAM-1 using lipopolysaccharide-induced RAW 264.7 cell models. The viability test was carried out in the concentration range of 0.49-1000 µg / mL. The pattern of inhibition of cell proliferation is influenced by concentration. The highest concentration that caused cell viability of 80% was the concentration of 86.46μg / ml. Crude fukoidan reduced ICAM-1 and VCAM-1 levels at concentrations of 50 and 25 μg / ml.. Percent inhibition of ICAM-1 at 50 µg / mL concentration was 61.04% compared to control and 74.26% at 25 µg / mL concentration. While the percent inhibition of VCAM-1 a